2015
DOI: 10.1002/bab.1441
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of O‐GlcNAcylation and involvement of PI3K/Akt1 pathway in the expression of oncogenic phenotypes of gastric cancer cells in vitro

Abstract: O-GlcNAcylation is a monosaccharide modification by a residue of N-acetylglucosamine (GlcNAc) attached to serine or threonine moieties on nuclear and cytoplasmic proteins. O-GlcNAcylation is dynamically regulated by O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA). Increasing evidence suggests that O-GlcNAcylation is involved in a variety of human cancers. However, the exact role of O-GlcNAcylation in tumor progression remains unclear. Here, we show that O-GlcNAcylation accelerates oncogenic phenotypes of gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 51 publications
(53 reference statements)
2
12
0
Order By: Relevance
“…Previous studies have demonstrated the major role of miRNA in the regulation of the PI3K/Akt pathway in tumor initiation and progression [18]. Here, we demonstrated that miR-495 could inhibit ESCC cell growth and metastasis in vitro and in vivo by downregulating Akt1.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Previous studies have demonstrated the major role of miRNA in the regulation of the PI3K/Akt pathway in tumor initiation and progression [18]. Here, we demonstrated that miR-495 could inhibit ESCC cell growth and metastasis in vitro and in vivo by downregulating Akt1.…”
Section: Discussionsupporting
confidence: 53%
“…To further explore the mechanisms underlying miR-495-mediated inhibition of ESCC cells ability, we examined whether miR-495 targeted Akt1. Akt1 is the crucial mediator of the PI3K/Akt signaling pathway and mediates various cellular functions in a number of tumor types, including gastric cancer [18], glioma [19], lung cancer [20], and ESCC [21]. In glioma patients, overexpression of Akt protein is correlated with later glioma grade and poor prognosis [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…It would be of interest to determine whether a synergistic effect between FAS and OGT exists in lipid rafts, accentuating their respective activities. This hypothesis is supported by reports showing that, in Drosophila ( 75 ), HepG2 cells ( 72 ), MCF7 cells ( 76 ), and recently in human gastric cancer cells ( 77 ), OGT activity is crucial for activating mitogen signaling pathways.…”
Section: Future Directionsmentioning
confidence: 59%
“…It is well-known that O-GlcNAcylation and its transferase OGT was elevated in gastric cancer and involved in the survival of gastric cancer cells [ 26 ]. And a growing amount of studies supported the critical roles of O-GlcNAcylation in gastric cancer metastasis [ 27 , 28 ]. O-GlcNAcylation not only induced the expression of matrix metalloproteinases to promote the tumour invasion, but also catalyzed EMT-related proteins to destabilize cell adhesions [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%